The Compliance of Motor Vehicle Taxpayers: An Experimental Research - Nahumury, Joicenda; Utama, I Wayan Wisnu; Suryaningrum, Diah Hari (JASF: Journal of Accounting and Strategic Finance, 2018)
This study aims to analyze the influence of motor vehicle taxpayers' trust in government authority and tax sanctions on motor vehicle taxpayer compliance. This research is experimental research with 76 accounting student participants who are taking a Taxation course. The analysis method uses ANOVA analysis. The results of the study prove that the trustworthiness of taxpayers with government authorities influences the compliance of taxpayers in carrying out their tax obligations. Conversely, tax sanctions do not affect taxpayer compliance. This result proves that taxpayers will be more compliant with their tax obligations if the government performs its functions as a state apparatus properly. The government with competent authority means that there is clear accountability about the use of tax returns; it can encourage the level of tax compliance.